Immortalization and characterization of human dental mesenchymal cells. Issue 5 (May 2015) - Huang, Yide; Yang, Yun; Jiang, Meiqin; Lin, Meizhen; Li, Shuiqin; Lin, Yao
Abstract Objectives Due to the rarity of human embryonic samples and limited proliferating capability of primary human dental mesenchymal cells, it is valuable to create an immortalized human dental mesenchymal cell line for studying dental mesenchymal cell differentiation and signalling pathways during detinogenesis in humans. Methods In this study, dental mesenchymal cells from human molar tooth germs at 19-week gestation were isolated and immortalized with pSV40. Single cell colonies were then selected by 96-well plate dilution. The immortalized cell line was characterized using immmunofluorescent microscopy, RT-PCR and Western blot for the expression of SV40 large T antigen and five genes specific for the mesenchymal stage during tooth development. The differentiation and mineralization activities of the immortalized and primary cells were compared using adipogenic and calcifying induction. Results The immortalized dental mesenchymal cell line displayed a higher proliferation rate, expressed several tooth-specific markers including Msx1, Pax9, Lhx6, Barx1, and Runx2, and maintained the ability to differentiate and form mineralized nodules. Conclusions Our results demonstrated that the immortalized human mesenchymal cell line retained the characteristics similar to primary human dental mesenchymal cells and can be used for studying the mechanisms of human dental mesenchymal cell differentiation and signalling pathways involved in human odontogenesis.